Novel functional hepatitis C virus glycoprotein isolates identified using an optimised viral pseudotype entry assay - Urbanowicz, Richard A.; King, Barnabas; Ball, Jonathan K.; McClure, C. Patrick; Tarr, Alexander W.; Mason, Christopher P. (Microbiology Society, 2016)
Retrovirus pseudotypes are a highly tractable model used to study the entry pathways of enveloped viruses. This model has been extensively applied to the study of the hepatitis C virus (HCV) entry pathway, pre-clinical screening of antiviral antibodies and for assessing the phenotype of patient-derived viruses using HCV pseudoparticles (HCVpp) possessing the HCV E1 and E2 glycoproteins. However, not all patient-isolated clones produce particles that are infectious in this model. This study investigated factors that might limit phenotyping of patient-isolated HCV glycoproteins. Genetically related HCV glycoproteins from individual patient quasispecies were discovered to behave very differently in this entry model. Empirical optimisation of the ratio of packaging construct and glycoprotein-encoding plasmid was required for successful HCVpp genesis for different clones. The selection of retroviral packaging construct also influenced the function of HCV pseudoparticles. Some glycoprotein constructs tolerated a wide range of assay parameters, while others were much more sensitive to alterations. Furthermore, glycoproteins previously characterised as unable to mediate entry were found to be functional. These findings were validated using chimeric cell-cultured HCV bearing these glycoproteins. Using the same empirical approach we demonstrated that generation of infectious ebolavirus pseudoviruses (EBOVpv) were also sensitive to the amount, and ratio, of plasmids used, and that protocols for optimal production of these pseudoviruses is dependent on the exact virus glycoprotein construct. These findings demonstrate that it is crucial for studies utilising pseudoviruses to conduct empirical optimisation of pseudotype production for each specific glycoprotein sequence to achieve optimal titres and facilitate accurate phenotyping.